Analisis Pendapatan Usahatani Padi Sawah pada Program Gerbang Pangan Serasi Kabupaten Tabanan - PEBRIANTARI, NI LUH ADE; USTRIYANA, I NYOMAN GEDE; SUDARMA, I MADE (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2016)
Abstract Analysis of Paddy Rice Farming Income on the Gerbang Pangan Serasi Program in Tabanan Regency Gerbang Pangan Serasi (GPS) is a program of agriculture sectorthat began in 2013 at Tabanan regency. This program is a pilot system of organic agriculture with purposeto increase agriculture products and improve environment. The purpose of this research is to know the difference between GPS program farming with conventional farming which had already carried out by farmers. In order to achieve the objectives of the research, analysis was conducted on the weaknesses and advantages of the GPS program also comparative analysis of the costs, revenues, and R/C ratio.The results showed that there are three shortcomings and five advantages of GPS program compared to conventional farming. Results of the analysis showed that conventional farming and GPS programs spend the same cost. Results of the revenue and R/C ratios analysis shows GPS program is better than conventional farming. Based on the overall results of the research can be concluded that the GPS program farming more profitable in economic terms than conventional farming. GPS program is a program that is suitable to replace conventional farming. Keywords: Gerbang Pangan Serasi program, conventional farming, organic agriculture.